Demographic Variables and Emotional Labor of Public Sector School Leaders - Tahira Bibi, Nasir Mahmood (PJE, 2023)
Emotional Labor theory of Hochschild, 1983 and Grandey, (2000, 2015 & 2017) provided the basis of the current research that gives the regulation of emotions at workplace the two dimensions of EL as Surface Acting and Deep Acting level of the school leaders. Emotional Labor Measurement Scale for School Leaders (ELMS-SL) was used to measure the EL level of the public sector school leaders. M